Estruturação do projeto do sistema de produção (PSP) como suporte às decisões de planejamento e controle em obras industrializadas - Oliveira, Maria Danielle Leão de (2022)
Lean Construction seeks to optimize production processes, proposing a change in management philosophy that supports the planning of activities, reduction of process flows, continuous improvement, and elimination of waste, among other aspects. The Last Planner Production Planning and Control System (LPS) is among the main contributions to construction management. Therefore, this study proposes improvements to Production System Design (PSD) and production planning and control for companies that build industrialized construction projects using LPS. The research method adopted was a case study, using participant observation, indirect observations through photographic reports, and documentary analysis. A company managing an enterprise for the chemical and pharmaceutical industry was identified as the subject of this work. The company's production planning and control model presented opportunities for improvement, such as the development of the LPS at all levels and in a collaborative manner. The structuring of the PSP is based on strategic decisions using planning tools and indicators that would allow for transparency of the plans drawn up, such as line of balance (LOB), deviation from the deadline and duration, and adherence to the plan of attack. The results showed that drawing up the PSP can help make strategic decisions, which can be fundamental to drawing up and developing more assertive planning. Furthermore, using visual tools can increase the transparency of planning and control processes. At the end of the study, a series of improvement actions related to PSP and production planning and control were presented. The proposed model can be used for similar types of projects and for construction companies that use the concepts of LPS and seek to improve their processes through strategic planning tools, such as PSP.